Resource allocation and prioritization in auditory working memory - Kumar, S; Joseph, S; Pearson, B; Teki, S; Fox, Z; Griffiths, T; Husain, M (Taylor and Francis, 2012)
A prevalent view of working memory (WM) considers it to be capacity-limited, fixed to a set number of items. However, recent shared resource models of WM have challenged this “quantized” account using measures of recall precision. Although this conceptual framework can account for several features of visual WM, it remains to be established whether it also applies to auditory WM. We used a novel pitch-matching paradigm to probe participants' memory of pure tones in sequences of varying length, and measured their precision of recall. Crucially, this provides an index of the variability of memory representation around its true value, rather than a binary “yes/no” recall measure typically used in change detection paradigms. We show that precision of auditory WM varies with both memory load and serial order. Moreover, auditory WM resources can be prioritized to cued items, improving precision of recall, but with a concomitant cost to other items, consistent with a resource model account.